EVALUATION OF SPATIAL VARIABILITY OF FERTILITY INDICATORS OF CHERNOZEM SOILS BY GEOSTATISTICAL METHODS - Polevoy, A.; Mikityuk, O.; Bozhko, L.; Barsukova, E. (Scientific Progress & Innovations, 2022)
The regularities of spatial variability of agrochemical and physical properties of chernozem soils (the content of humus, easily hydrolysable nitrogen, mobile forms of phosphorus, exchangeable forms of potassium, acidity, carbon content, bulk density and content of physical clay) in the east of Ukraine (project area "Dontsovka" (SP SVF "Agro", department "Dontsovka", Novopskovskiy district, Luhansk region). With the help of simple kriging, maps of the spatial distribution of agrochemical and physical indicators of soil fertility were built. It has been established that the most variable of all the agrochemical characteristics of the soil are the content of mobile forms of phosphorus and exchangeable forms of potassium. The coefficients of variation are 23.90 and 16.58 %, respectively, which is characterized as the average variability of the trait. The maps of the spatial distribution of these indicators are characterized by large spotting. Weak variability (less than 10 %) is typical for the content of humus and carbon in the soil. Most of the territory is occupied by fields with high and high humus content. The content of easily hydrolysable nitrogen in the soil and soil acidity are characterized by the weakest variation among the agrochemical indicators of the state of the soil. The spatial distribution of fields according to the content of readily hydrolysable nitrogen in the soil is similar to the distribution of fields according to the content of humus in the soil. The spatial distribution of soil acidity is fairly uniform. The physical characteristics of soil properties are also characterized by weak variation. Correlation analysis showed that the content of humus in the arable layer of the soil has a good positive relationship with the content of readily hydrolysable nitrogen in the soil (0.579), the amount of mobile forms of phosphorus in the soil (0.394), the amount of exchangeable potassium (0.471), the amount of carbon in the soil (0.9) and has an inverse relationship with the soil density (-0.649).